St. Theresa's recieves 2 architectural awards - Chuck Scardina:::photographer::: (1979)
A Desert Sun newspaper article containing a photograph of Winfred 'Wini' Cody accepting the Golden Palms award on behalf of Bill Cody, her late husband the architect.